2020
DOI: 10.1029/2019ja027598
|View full text |Cite
|
Sign up to set email alerts
|

Multievent Analysis of Oscillatory Motion of Medium‐Scale Traveling Ionospheric Disturbances Observed by a 630‐nm Airglow Imager Over Tromsø

Abstract: We present a comprehensive investigation on the propagation characteristics of duskside medium-scale traveling ionospheric disturbances (MSTIDs) using 630.0-nm airglow emissions over Tromsø (69.6°N, 19.2°E; magnetic latitude: 66.7°N). The unique points of our observation are (1) duskside MSTIDs primarily exhibited eastward motion under quiet conditions but turned to the westward direction associated with geomagnetic disturbances, (2) the westward moving MSTIDs again turned to the eastward direction when the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 64 publications
2
12
2
Order By: Relevance
“…In contrast to the observations presented in Yadav et al. (2020), there was no major change in the direction of MSTIDs during the current event. The authors suggest that the westward turning of MSTIDs was likely a result of a poleward‐directed magnetospheric electric field that is imposed on the ionosphere during intervals of enhanced geomagnetic activity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the observations presented in Yadav et al. (2020), there was no major change in the direction of MSTIDs during the current event. The authors suggest that the westward turning of MSTIDs was likely a result of a poleward‐directed magnetospheric electric field that is imposed on the ionosphere during intervals of enhanced geomagnetic activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Shiokawa et al (2013) presented a statistical analysis of high-latitude nighttime MSTIDs observed by all-sky airglow imagers in the European and Canadian sectors and suggested that they are linked to the auroral electric field and caused mainly by the Perkins and E-F coupling instabilities. While the current event is much stronger in magnitude (in terms of electric field strength and phase speed) compared to these previous reports, the mechanism shown in Figure 11 is in good agreement with Shiokawa et al (2012Shiokawa et al ( , 2013 and Yadav et al (2020) during geomagnetic disturbances. We can note from Figure 8, that the oscillations in the SuperDARN and GNSS TEC data sets are observed in the afternoon-midnight sector, between 15 and 20 MLT.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The G-type MSTIDs, which seem to be caused by gravity waves in the thermosphere, have the following characteristics in airglow images: (a) invading continuously into the aurora seen in the northern part of the airglow images, (b) having more sinusoidal phase structures, and (c) propagating uni-directionally, and not showing temporal change of the propagation direction. The former-type (I-type) MSTIDs have been reported by Shiokawa et al (2012) and Yadav et al (2020). The latter-type (G-type) MSTIDs have been reported by Shiokawa et al (2013), particularly at summertime in Athabasca in their analysis.…”
Section: Multi-event Analysis and Discussionmentioning
confidence: 84%
“…(2012) and Yadav et al. (2020). The latter‐type (G‐type) MSTIDs have been reported by Shiokawa et al.…”
Section: Multi‐event Analysis and Discussionmentioning
confidence: 95%